Modifications of the MUlti stimulus test with Hidden Reference and Anchor (MUSHRA) for use in audiology. (25th May 2018) - Völker, Christoph; Bisitz, Thomas; Huber, Rainer; Kollmeier, Birger; Ernst, Stephan M. A.
Abstract: Objective : Two modifications of the standardised MUlti Stimulus test with Hidden Reference and Anchor (MUSHRA), namely MUSHRA simple and MUSHRA drag&drop, were implemented and evaluated together with the original test method. The modifications were designed to maximise the accessibility of MUSHRA for elderly and technically non-experienced listeners, who constitute the typical target group in hearing aid evaluation. Design : Three MUSHRA variants were assessed based on subjective and objective measures, e.g. test–retest reliability, discrimination ability, time exposure and overall preference. With each method, participants repeated the task to rate the quality of several hearing aid algorithms four times. Study sample : Fifty listeners grouped into five subject classes were tested, including elderly and technically non-experienced participants with normal and impaired hearing. Normal-hearing, technically experienced students served as controls. Results : Both modifications can be used to obtain compatible rating results. Both were preferred over the classical MUSHRA procedure. Technically experienced listeners performed best with the modification MUSHRA drag&drop. Conclusions : The comprehensive comparison of the MUSHRA variants demonstrates that the intuitive modification MUSHRA drag&drop can be generally recommended. However, considering e.g. specific evaluation demands, we suggest a differentiated and careful application of listening test methods.